Implementation of Data Access Object Pattern in Bookkeeping System Development - Nuraminah, Ahlijati (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The bookkeeping system is vital for managing a catering business, and incorporating design patterns in software development, specifically the Data Access Object (DAO) Pattern, can enhance structure, flexibility, and efficiency. This study focuses on implementing the DAO Pattern in the catering bookkeeping system to improve data management and overall system performance. Utilizing a software development framework, the DAO Pattern facilitates CRUD operations (Create, Read, Update, Delete) on entities, ensuring flexibility. Tests validate data integrity and proper DAO functions. The system test results through unit testing showed that 96% of the features that implemented DAO were successfully implemented. This demonstrates significant benefits, with improved data management structure and centralized changes. Implementing the DAO Pattern in catering's bookkeeping system ultimately enhances structured data management and overall system performance, providing insights for software developers working on similar business applications.